Changes to the Editorial Board - Alamo, Jesus A. Del (IEEE electron device letters, 2023)
It is my pleasure to welcome Dr. Mina Rais-Zadeh to the Editorial Board of IEEE Electron Device Letters. A biography and picture of Dr. Rais-Zadeh can be found below. Her subject areas are compound semiconductor devices, materials, processing and packaging, sensors and actuators, and emerging technologies and devices